Evaluating Service Quality: A Qualitative Analysis of Suroboyo Bus Services on the Purabaya - Rajawali Route in Surabaya City - Rahayu, Putri (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Public transport is any form of transport to move passengers or goods from one place to another which is done by being hired and rewarded. This research was conducted with the aim of determining the quality of Suroboyo bus services that have been provided to the people of Surabaya City with the Purabaya - Rajawali route. The approach to this research refers to qualitative approaches and descriptive types of research. The research method used in this study is qualitative method with interview and observation data collection techniques. Data analysis is carried out in an inductive way descriptively – qualitatively. The theory used in this study is the theory of service quality from Parasuraman et al. (1988). The results of this study show that five indicators of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy have been well implicated by Suroboyo bus service providers with the Purabaya - Rajawali bus route. Even though it is considered quite qualified, Suroboyo bus officers still strive to improve service quality. In addition, officers can also maintain their hospitality by giving smiles and greetings to every passenger who comes. Smiles and greetings given by bus officers will have an impact on passengers so that they feel that they have been cared for and comfortable with the service provided by the officer.